The summation is the key

Calculus Level 5

3 3 7 7 11 11 5 5 9 9 13 13 \displaystyle \dfrac{\sqrt[3]{3} \sqrt[7]{7} \sqrt[11]{11} \dots}{ \sqrt[5]{5} \sqrt[9]{9} \sqrt[13]{13} \dots}

The expression above can be expressed in the form

exp ( π A [ ln ( [ Γ ( B C ) ] n π ) + γ ] ) \exp \Bigg( \dfrac{\pi}{A} \bigg[ \ln \bigg( \frac{ [\Gamma ( \frac{B}{C})]^n}{\pi} \bigg) + \gamma \bigg] \Bigg)

where A A , B B , C C , and n n are integers with gcd ( B , C ) = 1 \gcd(B,C)= 1 , with B B and C C positive. Determine A + B + C + n A+B+C+n .

Notations:

  • γ \gamma denotes the Euler-Mascheroni constant
  • exp ( f ( x ) ) = e f ( x ) \exp( f(x) ) = e^{ f(x) }
  • Γ ( x ) \Gamma(x) denotes the Gamma Function.


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Jun 22, 2017

Consider the Dirichlet beta function β ( x ) = n = 0 ( 1 ) n ( 2 n + 1 ) x \beta(x) \; = \; \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^x} Then β ( x ) = n = 0 ( 1 ) n + 1 ln ( 2 n + 1 ) ( 2 n + 1 ) x \beta'(x) \; = \; \sum_{n=0}^\infty \frac{(-1)^{n+1}\ln(2n+1)}{(2n+1)^x} and hence β ( 1 ) = n = 0 ( 1 ) n + 1 ln ( 2 n + 1 ) 2 n + 1 \beta'(1) \; = \; \sum_{n=0}^\infty \frac{(-1)^{n+1}\ln(2n+1)}{2n+1} and so the infinite product we want is e β ( 1 ) = e x p [ 1 4 π ( 2 ln 2 + 3 ln π 4 ln Γ ( 1 4 ) + γ ) ] = e x p [ 1 4 π [ ln ( 4 π 3 Γ ( 1 4 ) 4 ) + γ ] ] = e x p [ 1 4 π [ ln ( Γ ( 3 4 ) 4 π ) + γ ] ] \begin{aligned} e^{\beta'(1)} & = \mathrm{exp}\Big[\tfrac14\pi\Big(2\ln2 + 3\ln\pi - 4\ln\Gamma(\tfrac14) + \gamma\Big)\Big] \; = \; \mathrm{exp}\Big[\tfrac14\pi\Big[\ln\Big(\frac{4\pi^3}{\Gamma(\frac14)^4}\Big) + \gamma\Big]\Big] \; = \; \mathrm{exp}\Big[\tfrac14\pi\Big[\ln\Big(\frac{\Gamma(\frac34)^4}{\pi}\Big) + \gamma\Big]\Big] \end{aligned} making the answer 4 + 3 + 4 + 4 = 15 4+3+4+4=\boxed{15} .

Efren Medallo
Jun 22, 2017

Let us concatenate the product as follows, naming the product P P .

P = k = 1 ( 2 k + 1 ) ( 1 ) k + 1 / ( 2 k + 1 ) P = \displaystyle \prod\limits_{k=1}^{\infty} (2k+1)^{(-1)^{k+1} / (2k+1)}

If we'll take the logarithm of both sides, we'll get

ln P = k = 1 ( 1 ) k + 1 ln ( 2 k + 1 ) 2 k + 1 \ln P = \displaystyle \sum\limits_{k=1}^{\infty} (-1)^{k+1} \frac{ \ln (2k+1)}{ 2k+1}

The Malmsten-Kummer series expansion for γ \gamma is as follows:

γ = ln π 4 ln ( Γ ( 3 4 ) ) + 4 π k = 1 ( 1 ) k + 1 ln ( 2 k + 1 ) 2 k + 1 \gamma = \ln \pi - 4 \ln \big( \Gamma (\frac{3}{4}) \big) + \frac{4}{\pi} \cdot \displaystyle \sum\limits_{k=1}^{\infty} (-1)^{k+1} \frac{ \ln (2k+1)}{ 2k+1}

From here we can now see that

k = 1 ( 1 ) k + 1 ln ( 2 k + 1 ) 2 k + 1 = π 4 [ ln ( [ Γ ( 3 4 ) ] 4 π ) + γ ] \displaystyle \sum\limits_{k=1}^{\infty} (-1)^{k+1} \frac{ \ln (2k+1)}{ 2k+1} = \frac{\pi}{4} \bigg[ \ln \big( \frac{[\Gamma(\frac{3}{4})]^4}{\pi} \big) + \gamma \bigg]

Giving us 4 + 3 + 4 + 4 = 15 4+3+4+4 = 15 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...